A Sustainable E-Learning Ecosystem: Linking Readiness, Teaching Efficiency, Culture, and Employability - Boumedyen Shannaq; Said Almaqbali (Ital Publication, 2026)
This paper hypothesizes and justifies a Sustainable E-Learning Ecosystem Framework that incorporates the readiness, teaching efficiency, and cultural enablers to improve the reputation of the institution, as well as graduate competency and employability. The model that was built based on the data collected by higher education institutions, and which was run on the Partial Least Squares Structural Equation Modeling (PLS-SEM), displayed a high explanatory power with high path coefficients. The direct effects were strong: readiness had a positive impact on the teaching efficiency (b = 0.131, t = 3.649, p < 0.001), teaching efficiency had a significant impact on the e-learning adoption (b = 0.522, t = 13.729, p < 0.001), and the e-learning adoption had the impact on the student performance (b = 0.512, t = 13.734, p < 0.001). The highest influence on sustainability indicators had student performance and competence; competence was a strong predictor of the university's reputation (b = 0.581, t = 16.134, p < 0.001), and reputation led to job employment (b = 0.814, t = 46.630, p < 0.001). Other critical effects were also present, like TE - AeL - SP - SC - UR - JE (b = 0.100, t = 6.548, p < 0.001), which proved the cascading impact of drivers of operation on long-term outcomes. There were mixed outcomes in terms of cultural factors: the mediating effect of information culture on competence and reputation (b = 0.289, t = 7.556, p < 0.001) was significant, and organizational and national cultural moderation was not significant. Policy support and training were both found to have a good direct influence on teaching efficiency (Ps b = 0.380, t = 7.914; TP b = 0.387, t = 8.869; p < 0.001) but did not act as moderators. According to these results, readiness and teaching efficiency are identified as key drivers, and competence and reputation are key to sustainable education outcomes and employability.